INFLUENCE OF Bacillus subtilis IN NEMATODES BIOLOGICAL CONTROL AND PRODUCTION ASPECTS OF BEAN - Oliveira, G. R. F.; Silva, M. S.; Proença, S. L.; Bossolani, J. W.; Camargo, J. A.; Franco, F. S.; Sá, M. E. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Aiming to avoid the use of highly toxic chemical pesticides, the use of antagonistic microorganisms becomes a sustainable alternative for the control of nematodes. Bacillus subtilis, a rhizobacterium whose nematicidal potential has been reported in the literature, but which lacks studies on its performance for crops such as common bean. The objective of this work was to evaluate the effects of a commercial product (c.p.) based on Bacillus subtilis applied by foliar spraying (FS) and via seed treatment (ST) in nematode control and on productive aspects of common bean. Treatments employed: T1 - Control; T2 - 20 kg ha-1 of carbofuran via sowing furrow; T3 - 350 mL ha-1 of the c.p. via ST; T4 - 350 mL ha-1 of the c.p. via ST + 1.0 L ha-1 of the c.p. via FS; T5 - 350 mL ha-1 of the c.p. via ST + 2.0 L ha-1 of the c.p. via FS; T6 - 1.0 L ha-1 of c.p. via FS and T7 - ​​2.0 L ha-1 of c.p. via FS. The nematode population was evaluated; Number of pods per plant, number of grains per plant, number of grains per pod, mass of 100 grains and productivity. There were no significant results regarding the productive aspects of common bean for all treatments. Bacillus subtilis was effective in the biological control of nematodes (T3 and T7) at 30 days after sowing, as well as nematicide carbofuran (T2).